Precise Control of Green to Blue Emission of Halide Perovskite Nanocrystals Using Terbium Chloride as Chlorine Source - Wenqiang Deng (Nanomaterials, 2021)
CsPbClxBr3-x nanocrystals were prepared by ligand-assisted deposition at room temperature, and their wavelength was accurately adjusted by doping TbCl3. The synthesized nanocrystals were monoclinic and the morphology was almost unchanged after doping. The fluorescence emission of CsPbClxBr3-x nanocrystals was easily controlled from green to blue by adjusting the amount of TbCl3, which realizes the continuous and accurate spectral regulation in the range of green to blue. This method provides a new scheme for fast anion exchange of all-inorganic perovskite nanocrystals in an open environment at room temperature.